2012
DOI: 10.1039/c2dt30303e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the wavelength of electrochemiluminescence by anodic potential: a design using non-Kekulé-structured iridium–ruthenium luminophores

Abstract: Setting up spatially separated HOMO and LUMO regions in a non-Kekulé structured trinuclear Ir(III)-Ru(II)-Ir(III) system and using oxidative-reduction electrochemiluminescence leads to emissions that are not detected in photoluminescence. Moreover, the new design allows tuning of the wavelength of emission in a stepless fashion as a function of the selected potential range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…20 Zysman-Colman and co-workers 21,22 in another example observed a significant red-shift (535 to 610 nm) in the ECL spectrum of an iridium complex containing a dimethyl-amino bipyridine ligand, when a sufficiently high potential was applied such that the amine moiety was irreversibly oxidised, thus affecting a change in its electron withdrawing/donating character. Schmittel and co-workers 23 also reported a potential dependent ECL emission from a trinuclear Ir( iii )–Ru( ii )–Ir( iii ) system. Here, a small step-less hypsochromic shift in the ECL emission was observed in the range 611–649 nm due to variations in the contributions of the frontier orbitals to the excited state with increasing oxidation state.…”
Section: Introductionmentioning
confidence: 93%
“…20 Zysman-Colman and co-workers 21,22 in another example observed a significant red-shift (535 to 610 nm) in the ECL spectrum of an iridium complex containing a dimethyl-amino bipyridine ligand, when a sufficiently high potential was applied such that the amine moiety was irreversibly oxidised, thus affecting a change in its electron withdrawing/donating character. Schmittel and co-workers 23 also reported a potential dependent ECL emission from a trinuclear Ir( iii )–Ru( ii )–Ir( iii ) system. Here, a small step-less hypsochromic shift in the ECL emission was observed in the range 611–649 nm due to variations in the contributions of the frontier orbitals to the excited state with increasing oxidation state.…”
Section: Introductionmentioning
confidence: 93%
“…Schmittel et al 13 demonstrated that "non-Kekule-structured" trinuclear Ir(III)−Ru(II)−Ir(III) species were dependent upon the applied potential, enabling the wavelength of maximum ECL intensity to be tuned from 649 to 611 nm with increasing anodic scan range, although only the red color can be acquired. All these findings provide further support for our suggestion.…”
Section: ■ Introductionmentioning
confidence: 98%
“…6 Independently, pursuing a “lab‐on‐a‐molecule”7 design, Schmittel et al. have investigated the ECL behavior of oligonuclear Ir III ‐Ru II and Ir III ‐Ru II ‐Ir III systems with TPrA wherein the metals are electronically isolated but covalently attached 8. They demonstrated that in these systems different ECL and photoluminescence (PL) behavior exists and that multiple ECL emissions are possible through recombination of different radical cationic species with the co‐reactant.…”
Section: Introductionmentioning
confidence: 99%